Autoantibodies to citrullinated fibrinogen compared with anti-MCV and anti-CCP2 antibodies in diagnosing rheumatoid arthritis at an early stage: data from the French ESPOIR cohort. Issue 3 (12th May 2012) - Nicaise-Roland, Pascale; Nogueira, Leonor; Demattei, Christophe; de Chaisemartin, Luc; Rincheval, Nathalie; Cornillet, Martin; Grootenboer-Mignot, Sabine; Dieudé, Philippe; Dougados, Maxime; Cantagrel, Alain; Meyer, Olivier; Serre, Guy; et al.
Abstract : Objectives: To compare the performance of anticitrullinated peptides/protein antibodies (ACPA) detected by three immunoassays in the French ESPOIR cohort of patients with early rheumatoid arthritis (RA) and undifferentiated arthritis (UA) and to study the relationship between ACPA and disease activity. Methods: A diagnosis of RA (1987 American College of Rheumatology (ACR) criteria) was established at baseline in 497 patients and after a 2-year follow-up in 592 patients. At baseline, antibodies to citrullinated fibrinogen (AhFibA), antimutated citrullinated vimentin (anti-MCV) and anticyclic citrullinated peptide (anti-CCP2) were assayed and the individual and combined diagnostic sensitivities and predictive values of the tests were determined. Relationships between ACPA positivity and the 28-joint disease activity score and Health Assessment Questionnaire scores were analysed. Results: At a diagnostic specificity of at least 98%, the three tests exhibited similar diagnostic sensitivities (47–48.5%). When considering as positive patients with at least one positive test, the sensitivity increased to 53.5% with a probable loss of specificity. Among the patients classified as having UA at baseline, 30% were positive for one ACPA, the positive predictive values for RA of the three tests ranging from 73% to 80% but increasing when two tests were associated. Whatever the test used, the addition of ACPA positivity to the 1987 criteria enhanced their sensitivity by 6%, close to that of the 2010 ACR/European League Against Rheumatism (EULAR) criteria. Conclusions: In early arthritis, AhFibA, anti-MCV and anti-CCP2 showed similar diagnostic sensitivity with a high diagnostic specificity and a similar high positive predictive value for RA. Adding ACPA to the 1987 ACR criteria significantly increased the number of patients classified as having RA, confirming the validity of the recent inclusion of the serological criterion in the ACR/EULAR criteria.